The Global Research Trends on Food Waste at Healthcare Setting: A Bibliometric Analysis Using Scopus Database - Nurul Alia Aqilah Samiun; Nurul Huda Razalli; Suzana Shahar; Zahara Abdul Manaf; Zurina Kefeli@ Zulkefli; Jauharah Md Khudzari; Norshariza Jamhuri (Universiti Putra Malaysia Press, 2024)
Indexed by Scopus